Drafting the EU Charter - Schönlau, J. author. aut Link
XII, 213 p.
Keywords: This book gives a comprehensive account of the drafting of the EU Charter in the first Convention and shows the important contribution of this process to the constitutional development of the European Union. By drawing on a body of empirical data from the Convention in 1999-2000 it shows how the debates about a catalogue of fundamental rights for the EU prior to enlargement triggered a much wider discussion about the basis and basics of European integration. Thus it can shed new light on the EU's ongoing search for legitimacy.